LST1: a novel biomarker for efferocytosis in the co-occurrence of type 2 diabetes mellitus and clear cell renal cell carcinoma - Yang, Yuru; Chen, Tingting; Xu, Zhicheng; Cai, Jialing; Wang, Wenli; Pan, Lan; Cheng, Xiaotian; Wang, Andong (Frontiers in Immunology, 2025)
BackgroundThe rising global incidence of clear cell renal cell carcinoma (ccRCC) often coincides with metabolic disorders like type 2 diabetes mellitus (T2DM). However, the association between these two conditions remains unclear. This study aimed to identify common molecular pathways and novel biomarkers for the comorbidity of T2DM and ccRCC.MethodsUtilizing single-cell transcriptomic datasets from the GEO public database, this study identified heterogeneous cell characteristics and core subpopulations in T2DM and ccRCC. Immune infiltration was assessed using the GSEA algorithm, and a prognostic model was optimized through machine learning algorithms. Key genes were pinpointed in conjunction with the optimal model’s score. Subsequently, in vivo and in vitro comorbidity models were established to validate the pivotal role of these key genes in the comorbidity.ResultsSingle-cell sequencing analysis revealed that efferocytosis was notably active in dead cell clearance in T2DM. In ccRCC, macrophages regulated efferocytosis to facilitate antigen presentation, modulate inflammation, and promote intercellular communication. Integrating machine learning and transcriptome analysis, we identified LST1 as a pivotal regulatory gene in both T2DM and ccRCC (AUC> 0.745). This result suggests that LST1 is involved in regulating macrophage-mediated efferocytosis and immune communication. Analysis of immune infiltration suggests that LST1-mediated efferocytosis may influence ccRCC susceptibility or disease progression by sustaining immune signaling activation and disrupting regulatory balance, potentially stemming from early inflammation in T2DM. Validation through in vitro and in vivo experimental models further underscores the critical role of LST1 in disease advancement.ConclusionThis study initially identified LST1 as a pivotal regulatory factor in the co-occurrence of T2DM and ccRCC, emphasizing its essential involvement in the immune interaction within the hyperglycemia-induced microenvironment of ccRCC. These results not only elucidated the immunomodulatory role of LST1 in individual diseases but also delineated an immunological continuum bridging diverse conditions, providing a novel framework for investigating the immune pathways implicated in the concurrent presence of diabetes and malignancies.